The Influence Of Youtube on The Development of Islamic Religious Values on Early Children in Group B1 Idhata Palu Kindergarten - Nurhayati; Andi Agusniatih; Rafika (East Asian Journal of Multidisciplinary Research, 2022)
The problem in this study is that the development of children's Islamic religious values ​​has not developed as expected. This study aims to determine the development of children's Islamic religious values ​​using YouTube social media. This research method is quantitative with experimental research type. The research subjects were group B1 TK Idhata Palu, the number of students was 16 children consisting of 10 boys and 6 girls. Data collection techniques were carried out through observation, documentation, and interviews. Data management is done by using percentage technique. Based on the results of the recapitulation of the development of children's Islamic religious values ​​before being given treatment in the form of using YouTube social media, in the Wudhu aspect there are 12.5% ​​in the BSH category, 43.75% in the MB category, 43.75% in the BB category, in the prayer aspect there are 12 , 5% in the BSH category, 37.5% in the MB category, 50% in the BB category, and in the Hijaiyyah Letter Recognition aspect there are 18.75% in the BSH category, 43.75% in the MB category, 37.5% in the BB category . After being given treatment, the results obtained, in the Wudhu aspect there were 12.5% ​​in the BSB category, 25% in the BSH category, 31.25% in the MB category, 31.25% in the BB category, in the prayer aspect there were 6.25% in the category BSB, 31.25% in the BSH category, 37.5% in the MB category, 25% in the BB category, and in the Hijaiyyah Letter Recognition aspect there are 18.75% in the BSB category, 31.25% in the BSH category, 25% in the MB category, 25% in BB category. The average of the three aspects observed before treatment in the BSH and MB categories was 56.25%, after treatment 72.92% in the BSB, BSH, and MB categories.